Digital marketing communication for book publishing in Nigeria: exploring the role of social media strategy / Abdulrasheed Adebola Afolabi and Izzal Asnira Zolkepli - Afolabi, Abdulrasheed Adebola; Zolkepli, Izzal Asnira (Faculty of Information Management, 2023)
Concerns have been raised about the growth of the book publishing sector in developing nations. A thread of the conversation in Nigeria centers on the expansion of the book publishing industry beyond the textbook publishing, with solutions such as exploring new markets and consolidating on current market niches coming up. A number of studies have documented the influence of digital technologies on book marketing practices in Nigeria. However, there is a knowledge gap on the role of strategy in the use of social media for marketing communication in that context. By undertaking a literature review of relevant studies from 2001 to present, this study examines; i) trends in digital marketing practices in book publishing and ii) how social media strategy functions as a unifying factor among the variety of online marketing tools available to book publishers. The findings demonstrate how book publishers employ websites, SEO, social media, e-mail marketing and content marketing (blogging) for online marketing. The use of strategy by publishers to improve social media marketing activities and increase return on investment is also reported.